Spatial analysis of cyclist mobility patterns using geovisualization to improve public bike-share system in a small size city - Perotti, Fabián Rodolfo (2019)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies